If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(n-4)=-2(n+2)
We move all terms to the left:
-4(n-4)-(-2(n+2))=0
We multiply parentheses
-4n-(-2(n+2))+16=0
We calculate terms in parentheses: -(-2(n+2)), so:We get rid of parentheses
-2(n+2)
We multiply parentheses
-2n-4
Back to the equation:
-(-2n-4)
-4n+2n+4+16=0
We add all the numbers together, and all the variables
-2n+20=0
We move all terms containing n to the left, all other terms to the right
-2n=-20
n=-20/-2
n=+10
| m+(-1)=-4 | | 7(x+13)=-21 | | 3(5x+8)=-22+16 | | 4x(2x-1)=20 | | 3(7x+11)=9x-3 | | 9x=12+13x | | 6t-55t=105 | | -2(4-3y)=-50 | | −6r=24 | | 5x-8=5x+7 | | 4r+1=12+7r+4+3 | | 3(x-8)-8=-32 | | F(24)=3x-1 | | b3+ 12=14 | | 12x-1=71 | | 1/3x^2-5=7 | | 4+3x/3+5-x/2=5/6 | | 5(h+2)+h=20 | | 3(2x+8)=41+11 | | n-5(2n-9)=2(n-3)+6n | | -3=7+k | | 5/2x=-2x | | x+1=7+2x | | 6(x-10)=-30 | | 3x-5=14x-1 | | 15-5x=6x+3+-2x | | 11/5x3/7=7x+1/2 | | (2x+6)+(5x-1)=9x-3 | | 14(2c-4)=4c-8 | | -6x+14=2(3x-7) | | -7(7x+8)=-5 | | 30/1.5xX=5 |